IMPLEMENTASI PEMBELAJARAN DARING DI UPT SMP NEGERI 20 GRESIK - Siti Nur Aini; Ertien Rining Nawangsari (Jurnal Penelitian Administrasi Publik, 2021)
The implementation of education in Indonesia today, cannot be separated from the achievement of goals that become a benchmark for successful implementation. The implementation of education is currently being faced with the COVID-19 pandemic which has forced the government to close face-to-face teaching and learning activities and create a new policy, namely online learning. This study aims to determine and describe how the implementation of online learning at UPT SMP Negeri 20 Gresik. The research method used is a qualitative method. The location of the research was conducted at UPT SMP 20 Gresik. The focus of this research is based on the theory of implementation of George C. Edward III which includes 1.) Communication, 2). Resources, 3). Disposition, 4). Bureaucratic Structure. Data collection techniques were obtained through observation, interviews and documentation. The results obtained in this study are: 1). Communication in the implementation of online learning is not optimal on the transmission factor, because the socialization given seems sudden so that the preparation problem has not been maximized. 2). Resources in the implementation of online learning are also still constrained by the quota assistance provided by the government. 3). The disposition of the implementor regarding online learning has not been implemented optimally, because there are still constraints on the cognitive indicators experienced by students. 4). The organizational structure in the implementation of online learning refers to the technical guidelines for the implementation of online learning, with the RPP being made by the teacher as a guide in carrying out learning. The conclusion in this study is that the implementation of online learning at UPT SMP Negeri 20 Gresik has not been implemented properly, because there are still obstacles in several indicators of successful implementation.